RF Transceiver Design For 3G Cellular Communications - Wong, Sew Kin (2002)
A Radio frequency (RF) transceiver is designed for UMTS Terrestrial Radio Access (UTRA) Frequency Division Duplexing (FDD) Wideband-Code Division Multiple Access (W-CDMA) user equipment (UE) and the respective performance analysis is presented in this thesis. The performance analysis is conducted through simulation and measurement towards the 3GPP specifications. This Rf front end mobile transceiver provides the function of modulation and demodulation of the 3G cellular communications digital signal in the air link. It is implemented with a commercial standard dual conversion transmitter operating at 1920MHz to 1980MHz and a heterodyne receiver operating at 2110MHz to 2170MHz.